Pathways between under/unemployment and health among racialized immigrant women in Toronto. Issue 1 (2nd January 2017) - Premji, Stephanie; Shakya, Yogendra
ABSTRACT: Objective . We sought to document pathways between under/unemployment and health among racialized immigrant women in Toronto while exploring the ways in which gender, class, migration and racialization, as interlocking systems of social relations, structure these relationships. Design . We conducted 30 interviews with racialized immigrant women who were struggling to get stable employment that matched their education and/or experience. Participants were recruited through flyers, partner agencies and peer researcher networks. Most interviews (21) were conducted in a language other than English. Interviews were transcribed, translated as appropriate and analyzed using NVivo software. The project followed a community-based participatory action research model. Results . Under/unemployment negatively impacted the physical and mental health of participants and their families. It did so directly, for example through social isolation, as well as indirectly through representation in poor quality jobs. Under/unemployment additionally led to the intensification of job search strategies and of the household/caregiving workload which also negatively impacted health. Health problems, in turn, contributed to pushing participants into long-term substandard employment trajectories. Participants' experiences were heavily structured by their social location as low income racialized immigrant women. Conclusions . Our study provides needed qualitative evidence on the gendered and racialized dimensions of under/unemployment, and adverse health impacts resulting from this. Drawing on intersectional analysis, we unpack the role that social location plays in creating highly uneven patterns of under/unemployment and negative health pathways for racialized immigrant women. We discuss equity informed strategies to help racialized immigrant women overcome barriers to stable work that match their education and/or experience.